Resolusi Konflik Pertanahan di Kota Bandar Lampung - Artha Silvia Nababan; Kushandajani Kushandajani; Turtiantoro Turtiantoro (Journal of Politic and Government Studies, 2015)
Land is very essential issue because it concerns with life of many people to build houses, business area. To consider the importance of the land, requisition of the land often resulted in the conflict by competition to manage or to hold the land for farming and the situation produced the tension among the peoples themselves. Bandar Lampung City, it has often suffered from the land conflict among peoples because there was no absolute solution for the land conflict itself. This was a research of analytical descriptive. It means, it was an analysis of data based on field research related to law theories especially in Land Law. The approach used was to present and analyze the problems found in fields to have the conclusion as the core of discussion. The data analysis was accomplished by concluding primary and secondary data and then evaluated and analyzed qualitatively to discuss the problems based on field data and statutes related to land law to get new description and to support the existing description to answer the problem and to draw significant conclusion. The settlement of conflict in Bandar Lampung City was accomplished through Mediation by Land Office of Bandar Lampung City . Land Office of Bandar Lampung city role as mediators of land disputes that lead the mediation process with the aim of both parties to the dispute to reach a mutual agreement. From this research, it is known that the Land Office of Bandar Lampung City has to perform its role in accordance with the duties and functions of the Land Office as mediators of land disputes. Keywords : Land conflicts Resolution, Land office, Bandar Lampung City